Effectiveness rabbitt's manure liquid organic fertilizer dosage and time of aplication on purple sweet corn - Rahmatika, Widyana; Andayani, Retno Dwi (Universitas Trunojoyo Madura, 2024)
Purple corn is a commodity that is not been widely cultivated in Indonesia. The nutritional value of purple corn is higher than yellow and white corn. Purple corn contains anthocyanin components that act as antioxidant compounds in the prevention of several diseases such as cancer, diabetes, cholesterol, and coronary heart disease. Purple corn can also be used as a raw material for making additional food. The objective of this study was to investigate the interaction effect of rabbit manure liquid fertilizer (LOF) concentration and application time on the growth and yield of purple sweet corn. The research was carried out at the Integrated Field Laboratory, Faculty of Agriculture, Kadiri Islamic University from September to November 2021. This factorial experiment was arranged in a randomized block design consisting of 2 factors. The first factor was the concentration of LOF (U) which consisted of 4 levels, namely U0 is 0 mL/plant, U1 is 20 mL/plant, U2 is 30 mL/plant, and U3 is 40 mL/plant. The second factor was the application time of rabbit LOF (A) involving 2 levels, namely A1 is 1 week before planting and A2 is 1 week after planting. The combination of both factors resulted in 8 treatment combinations. Each treatment was replicated 3 times. The results showed that there was no interaction between the concentration of rabbit’s manure LOF and application time on the growth and yield of purple sweet corn. The concentration of LOF had a significant effect on cob weight, while the time of application had a significant effect on cob weight without cob and sweetness levels.